2012
DOI: 10.3233/jad-2012-111940
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Neurotoxicity of Homocysteine Thiolactone in Mice: Evidence for a Protective Role of Paraoxonase 1

Abstract: Homocysteine (Hcy)-thiolactone is toxic, induces epileptic seizures in rodents, and has been implicated in Alzheimer’s disease. Paraoxonase 1 (Pon1), a component of high-density lipoprotein, hydrolyzes Hcy-thiolactone in vitro. Whether this reflects a physiological function and whether Pon1 can protect against Hcy-thiolactone toxicity was unknown. Here we show that Hcy-thiolactone was elevated in brains of Pon1−/− mice (1.5-fold, p = 0.047) and that Pon1−/− mice excrete more Hcy-thiolactone than wild type anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…These results collectively indicated that PON1 was primarily involved in M1 formation from 2-oxo-ticlopidine. PON1 is known to be involved in the hydrolysis of lactone or thiolactone derivatives such as pilocarpine (Billecke et al, 2000;Hioki et al, 2011) and homocysteine thiolactone (Borowczyk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results collectively indicated that PON1 was primarily involved in M1 formation from 2-oxo-ticlopidine. PON1 is known to be involved in the hydrolysis of lactone or thiolactone derivatives such as pilocarpine (Billecke et al, 2000;Hioki et al, 2011) and homocysteine thiolactone (Borowczyk et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced PON1 activity is linked to cardiovascular disease [7,8]. In mice, Pon1 gene deletion impairs urine concentrating ability, which leads to a polyuria phenotype [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hcy is a negative determinant of HDL and PON1 [17] and reduces Apoa1 and Pon1 gene expression [18]. HDL and purified PON1 detoxify Hcy-thiolactone [19] and protect against protein Nhomocysteinylation [9,20]. N-Homocysteinylation causes protein damage and is linked to kidney and cardiovascular diseases (reviewed in [21]).…”
Section: Introductionmentioning
confidence: 99%
“…It is a homocysteine-thiolactonase. [31][32][33][34] PON1 evolved from bi-functional enzymes that act as homoserine lactones which are quorum-sensing molecules employed by many gram-negative bacteria. PON1 is thereby a component of the innate immunity.…”
Section: Introductionmentioning
confidence: 99%